The Role of Information Literacy as Moderation Between Entrepreneurial Orientation and Innovation Performance - Arifin, Yoke Ranlym; Utomo, Prio; Kembaren, Julbintor (ADI Publisher, 2021)
Background research of this study aims to determine the role of information literacy (IL) on the relationship between Entrepreneurial Orientation and Innovation Performance at the Manufacturing Company. This research is considered important because the trend is growing rapidly so that it requires companies to innovate in order to survive in the face of various challenges in the future. Based on previous research, innovation grows because of the entrepreneurial spirit such as Risk Taking, Innovativeness and Proactiveness. The company should have Information Literacy (IL) in order to have a correct understanding of what is happening in society. This research can also be a reference for Manufacturing Company so that they can see opportunities from the role of Information Literacy and develop an entrepreneurial spirit in every employee who works so that they can produce Innovation Performance. The method / theory of this study used PLS SEM (Partial Least Square Structural Equation Modeling) with SmartPLS version 3.2.9. The author collects data from 150 respondents. The results of the study indicate that the entrepreneurial orientation of employees consisting of innovativeness, proactiveness and risk taking can help companies produce innovation performance. However, information literacy has not played a significant role as a moderator between intrapreneurial orientation and innovation performance. The conclusion of the research is that entrepreneurial orientation produces quality human resources because it can be a source of innovation.